Westward dharma : Buddhism beyond Asia - Prebish, Charles S.; Baumann, Martin, 1960- (University of California Press, 2002)
The first authoritative volume on the totality of Buddhism in the West, Westward Dharma establishes a comparative and theoretical perspective for considering the amazing variety of Buddhist traditions, schools, centers, and teachers that have developed outside of Asia.